The University of Strathclyde summer experience: the impact of a widening access residential summer programme for children in care - Iain Mitchell (Scottish Journal of Residential Child Care)
The Innovative Routes to Learning (IRL) unit at the University of Strathclyde ran a three-day on-campus residential programme for children from a looked after (care) background from three Glasgow City Council schools during summer 2013, designed to build pupils' academic confidence and raise their awareness of and aspiration to progress on to university. Evaluation of the programme shows very positive results in a number of areas, including pupils' aspirations and confidence to undertake university-level study, pupils' knowledge of higher education, and attitude towards school-work. Participants also benefitted greatly from working with student mentors and other young people from different areas. In order to maximise the benefits of such programmes it is important to bear in mind issues around correct targeting of participants, effective communication between stakeholders and ensuring the programme is set within an extended, co-ordinated programme of support.